OSTWALD RIPENING OF GARNET IN HIGH P/T METAMORPHIC ROCKS - Miyazaki K. (My University, 1991)
This paper presents a theoretical formulation of Ostwald ripening of garnet and discusses the importance of the process during high pressure and low temperature (high P/T) metamorphism. The growth rate of garnet due to Ostwald ripening is formulated for the system consisting of minerals and an intergranular medium. Crystal size distribution (CSD) of garnets are examined and compared with the theoretical distribution for Ostwald ripening. Two types of CSDs are recognized. One is consistent with the theoretical prediction of size distribution while the other is wider than the theoretical distribution. The former CSD applies to samples in which garnets show homogeneous spatial distributions. The latter CSD applies to samples in which garnets show heterogeneous spatial distributions such as in clusters or layers. These relations suggest that the heterogeneity of spatial distributions results in a heterogeneity of concentration of garnet, causing the wide distributions. The mean diameter (dg) has a large variation in samples having narrow distributions. Ostwald ripening explains well the similar patterns of CSD in these samples with different dg because of a scaling law. Compositional profiles of garnets with different size are consistent with Ostwald ripening rather than nucleation and growth kinetics. This suggests that the CSDs result from Ostwald ripening. Magnitude of heating rate will determine which mechanism controls CSD. Nucleation and growth kinetics are dominant when heating rate is large. On the other hand, Ostwald ripening is dominant when heating rate is small. CSDs of garnets in high P/T metamorphic rocks are consistent with the latter case.